Question
upstudy study bank question image url

\( \left. \begin{array} { l l } { 3 } & { 3 ^ { x ^ { 2 } + 2 } = 9 \cdot \frac { 1 } { 27 ^ { x } } } \\ { 4 } & { 5 ^ { x ^ { 2 } - 1 } \cdot \frac { 1 } { 25 } = 25 ^ { x } } \\ { 5 } & { 2 ^ { 2 x } \cdot 4 ^ { x + 1 } = 1 } \\ { 6 } & { 12 ^ { x } \cdot 12 ^ { x } = 144 } \\ { 7 } & { 2 ^ { x ^ { 2 } \cdot 2 ^ { x ^ { 2 } - 2 } + 1 = 65 } } \\ { 8 } & { \frac { 4 ^ { x + 1 } \times ( \frac { 1 } { 4 } ) ^ { - x } } { 2 ^ { 2 x + 1 } } = \frac { 1 } { 32 } } \\ { 9 } & { 81 \cdot 9 ^ { x - 1 } = \frac { 1 } { 27 } } \\ { 10 } & { 10 ^ { 2 x ^ { 2 } } \cdot 10 ^ { x + 1 } = 10000 } \end{array} \right. \)

Ask by Gough Barnett. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the solutions for each equation: 1. \( x = -3 \) or \( x = 0 \) 2. \( x = -1 \) or \( x = 3 \) 3. \( x = -0.5 \) 4. \( x = 1 \) 5. Cannot solve due to unsupported calculation 6. \( x = -3 \) 7. \( x = -2.5 \) 8. \( x = -1.5 \) or \( x = 1 \)

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(12^{x}\times 12^{x}=144\) - step1: Multiply the terms: \(12^{2x}=144\) - step2: Rewrite in exponential form: \(12^{2x}=12^{2}\) - step3: Set the exponents equal: \(2x=2\) - step4: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step5: Divide the numbers: \(x=1\) Solve the equation \( 2^{2x} \cdot 4^{x+1}=1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{2x}\times 4^{x+1}=1\) - step1: Multiply the terms: \(2^{4x+2}=1\) - step2: Rewrite in exponential form: \(2^{4x+2}=2^{0}\) - step3: Set the exponents equal: \(4x+2=0\) - step4: Move the constant to the right side: \(4x=0-2\) - step5: Remove 0: \(4x=-2\) - step6: Divide both sides: \(\frac{4x}{4}=\frac{-2}{4}\) - step7: Divide the numbers: \(x=-\frac{1}{2}\) Solve the equation \( 81 \cdot 9^{x-1}=\frac{1}{27} \). Solve the equation by following steps: - step0: Solve for \(x\): \(81\times 9^{x-1}=\frac{1}{27}\) - step1: Multiply the terms: \(9^{x+1}=\frac{1}{27}\) - step2: Rewrite in exponential form: \(3^{2\left(x+1\right)}=3^{-3}\) - step3: Set the exponents equal: \(2\left(x+1\right)=-3\) - step4: Divide both sides: \(\frac{2\left(x+1\right)}{2}=\frac{-3}{2}\) - step5: Divide the numbers: \(x+1=-\frac{3}{2}\) - step6: Move the constant to the right side: \(x=-\frac{3}{2}-1\) - step7: Subtract the numbers: \(x=-\frac{5}{2}\) Solve the equation \( \frac{4^{x+1} \times (\frac{1}{4})^{-x}}{2^{2x+1}}=\frac{1}{32} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{4^{x+1}\left(\frac{1}{4}\right)^{-x}}{2^{2x+1}}=\frac{1}{32}\) - step1: Reduce the fraction: \(2^{2x+1}=\frac{1}{32}\) - step2: Rewrite in exponential form: \(2^{2x+1}=2^{-5}\) - step3: Set the exponents equal: \(2x+1=-5\) - step4: Move the constant to the right side: \(2x=-5-1\) - step5: Subtract the numbers: \(2x=-6\) - step6: Divide both sides: \(\frac{2x}{2}=\frac{-6}{2}\) - step7: Divide the numbers: \(x=-3\) Solve the equation \( 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x^{2}+2}=9\times \frac{1}{27^{x}}\) - step1: Simplify: \(3^{x^{2}+2}=3^{-3x+2}\) - step2: Set the exponents equal: \(x^{2}+2=-3x+2\) - step3: Cancel equal terms: \(x^{2}=-3x\) - step4: Move the expression to the left side: \(x^{2}-\left(-3x\right)=0\) - step5: Add or subtract both sides: \(x^{2}+3x=0\) - step6: Factor the expression: \(x\left(x+3\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x=0\\&x+3=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=0\\&x=-3\end{align}\) - step9: Rewrite: \(x_{1}=-3,x_{2}=0\) Solve the equation \( 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{x^{2}-1}\times \frac{1}{25}=25^{x}\) - step1: Multiply the terms: \(5^{x^{2}-3}=25^{x}\) - step2: Rewrite the expression: \(5^{x^{2}-3}=5^{2x}\) - step3: Set the exponents equal: \(x^{2}-3=2x\) - step4: Move the expression to the left side: \(x^{2}-3-2x=0\) - step5: Factor the expression: \(\left(x-3\right)\left(x+1\right)=0\) - step6: Separate into possible cases: \(\begin{align}&x-3=0\\&x+1=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-1\end{align}\) - step8: Rewrite: \(x_{1}=-1,x_{2}=3\) Solve the equation \( 10^{2x^{2}} \cdot 10^{x+1}=10000 \). Solve the equation by following steps: - step0: Solve for \(x\): \(10^{2x^{2}}\times 10^{x+1}=10000\) - step1: Multiply: \(10^{2x^{2}+x+1}=10000\) - step2: Rewrite in exponential form: \(10^{2x^{2}+x+1}=10^{4}\) - step3: Set the exponents equal: \(2x^{2}+x+1=4\) - step4: Move the expression to the left side: \(2x^{2}+x+1-4=0\) - step5: Subtract the numbers: \(2x^{2}+x-3=0\) - step6: Factor the expression: \(\left(x-1\right)\left(2x+3\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x-1=0\\&2x+3=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=1\\&x=-\frac{3}{2}\end{align}\) - step9: Rewrite: \(x_{1}=-\frac{3}{2},x_{2}=1\) Here are the solutions for each of the equations provided: 1. **Equation:** \( 3^{x^{2}+2} = 9 \cdot \frac{1}{27^{x}} \) **Solution:** \[ x_{1} = -3, \quad x_{2} = 0 \] 2. **Equation:** \( 5^{x^{2}-1} \cdot \frac{1}{25} = 25^{x} \) **Solution:** \[ x_{1} = -1, \quad x_{2} = 3 \] 3. **Equation:** \( 2^{2x} \cdot 4^{x+1} = 1 \) **Solution:** \[ x = -\frac{1}{2} \quad \text{(or } x = -0.5\text{)} \] 4. **Equation:** \( 12^{x} \cdot 12^{x} = 144 \) **Solution:** \[ x = 1 \] 5. **Equation:** \( 2^{x^{2} \cdot 2^{x^{2}-2}} = 65 \) **Solution:** \[ \text{Error: Unsupported calculation} \] 6. **Equation:** \( \frac{4^{x+1} \times \left(\frac{1}{4}\right)^{-x}}{2^{2x+1}} = \frac{1}{32} \) **Solution:** \[ x = -3 \] 7. **Equation:** \( 81 \cdot 9^{x-1} = \frac{1}{27} \) **Solution:** \[ x = -\frac{5}{2} \quad \text{(or } x = -2.5\text{)} \] 8. **Equation:** \( 10^{2x^{2}} \cdot 10^{x+1} = 10000 \) **Solution:** \[ x_{1} = -\frac{3}{2}, \quad x_{2} = 1 \quad \text{(or } x_{1} = -1.5, x_{2} = 1\text{)} \] If you need further assistance or explanations for any specific equation, feel free to ask!

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

Let's dive into the world of exponents! Did you know that exponents give us a way to express repeated multiplication of the same number? For instance, \(3^2\) means \(3 \times 3\). This concept dates back over 4,000 years to the ancient Babylonians, who had their own methods of dealing with powers in mathematics. Fast forward to today, exponents are foundational in fields like computer science and physics—where they help us understand everything from algorithms to atomic structures! Now, if you're tackling these equations, here's a fun tip: when you have bases that are not the same, try rewriting them as powers of a common base. For example, in \(27\) can be expressed as \(3^3\), allowing you to simplify your calculations. And remember, a common mistake is misapplying the exponent rules, especially when distributing exponents over addition or subtraction. Just be cautious and double-check your steps for a smoother problem-solving process!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy